Development and landscape of maintenance therapy after first-line treatment of advanced or metastatic urothelial carcinoma - Liu, Zengguang; Cong, Xiaofeng; Chen, Chen; Yin, Jiaxin; Liu, Ziling (Frontiers in Immunology, 2025)
Overall survival (OS) in patients with advanced or metastatic urothelial carcinoma (UC) is not optimistic. For a long time, the standard platinum-based chemotherapy has been one of the preferred treatment strategies. Despite the high initial objective response rate (ORR) to first-line chemotherapy in patients with metastatic UC, the rate of achieving complete response (CR) is low, and most patients will relapse within one year after first-line treatment. To further improve the OS of patients with metastatic UC, the success of the CheckMate901 and EV302 studies has brought new therapeutic options for the first-line treatment of these patients. Maintenance or consolidation therapy after first-line treatment is also important to improve the OS of patients with advanced UC. Maintenance therapy after first-line treatment of metastatic UC has undergone a long period of development until the success of the JAVELIN Bladder100 study. For the first time, this study established the application of avelumab as maintenance therapy after first-line platinum-containing chemotherapy. The aim of this paper is to review the development process of avelumab-based maintenance therapy after first-line treatment of advanced or metastatic UC and explore future options for maintenance therapy in patients with advanced or metastatic UC in the light of new first-line treatment options.